STRATEGI, AGEN, DAN POSISI EMHA AINUN NADJIB DI ARENA SASTRA DAN ARENA SOSIAL - Latief S. Nugraha (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
This research is conducted to prove about Emha Ainun Nadjib’s position, strategies and employment as a agent in the literature and social field. This study uses the sociological literature theor y proposed by Pierre Bourdieu to analyze the problems. The result of the study shows that Nadjib cannot achieve his current position by relying only on his literary works, but also by relying on his social and political movements which are done in literature and social field. Nadjib successfully manages capital with reproduction strategy and reconvention strategy to apply his ideas. Those strategies are employed to accumulate capital for achieving , maintaining , and improving social recognition in the field of national literature which further creates trajector y to a wider social field. The rest, the role of agents around him also have a major influence in cementing his name and position in the constellation of literature and social field in both nationaland international.Keywords: Emha Ainun Nadjib, the field of cultural production, agents, field of literature, field of social.